APPLICATION OF NEW TECHNOLOGIES AND THEIR IMPORTANCE IN IMPROVING THE QUALITY OF DAIRY AND MEAT PRODUCTS ON THE FARM - Sobirova Feruza Ilhomjonovna (Journal Park Publishing, 2023)
The article discusses the results of the use of new innovative technologies to improve the quality of milk and meat products in the farms of our country, the implementation of best practices and modern technologies, and the effectiveness of increasing the economic efficiency and competitiveness of the livestock industry. As a result of the analysis, the increase in the number of the population of our country was analyzed to meet the demand for livestock products, to further increase the volume of production of meat, milk, eggs and other products in the domestic consumer markets, and to ensure price stability.
Keywords: Farming, milk, quality, food, consumer, innovation, material technology.